Strength of Palm Oil Fly Ash (POFA) incorporated with sawdust in concrete pavement / Jamilah Abd Rahim ... [et al.] - Abd Rahim, Jamilah; Abdul Aziz, Nurul Faiizin; Mohktar, Hamizah; Harun, Mohamad Hafiz (2022)
Jengka is the largest FELDA in Malaysia located in the state of Pahang Darul Makmur. Jengka consists of 25 FELDA plans which are palm and rubber producers. The production of Palm Oil Fly Ash (POFA) is rising every year, it is disposed of in landfills, now becoming an important environmental disposal issue. The government needs to focus on assigning more hectares of land for disposal of these huge amounts of waste, and financial losses are also increased for transporting as well as maintenance purposes of these wastes. The pollution problem is increased in this sector which includes the annual production of 2.6 million tonnes of solid waste in the form of POFA. The large quantity of this waste can create an environmental problem if disposed of in the wrong way. However, reduction of dumped waste and environmental sustainability can be ensured by proper consumption or recycling of these materials. Therefore, this research innovation used waste material of POFA in a concrete mixture to produce eco pavement block. The compliance testing for the concrete mix was investigated. The optimal mix design proportion in order to increase the compressive strength, density and durability of POFA concrete was established. Mix proportion containing 5 % POFA mixtures exhibited substantially higher rates of strength gain as compared with other mixtures containing 10 % and 15 % of POFA. The workability of POFA concrete increases, thus, the permeability and bleeding in concrete decrease. Implementation of POFA waste not only decreases environmental damage but also saves concrete materials.